Some Results in Nonsmooth Optimization (Journal of Computational Mathematics, 1987)
Some main results in nondifferentiable optimization are reviewed. In section 2, we discuss subgradient methods. Section 3 is about the cutting plane method and the bundle methods are studied in section4. Trust region methods for composite nonsmooth optimization are discussed in section 5.